Hyperexplexia or Hereditary Stiff Baby Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
The stiff baby syndrome and its diagnostic distinction from epilepsy is reviewed from the Service de Neuronatologie, Pavillon de la Mere et l'Enfant, Nantes, France.